IMPLEMENTING GOOGLE CLASSROOM-BASED COGNITIVE STRATEGY OF ENGLISH FOR SPECIFIC PURPOSES - Rizky Eka Prasetya (IAIN Syekh Nurjati Cirebon, 2021)
Pedagogical language has shifted dramatically and significantly in these recent pandemic eras. Lecturers could be implemented and adjusted the face-to-face teaching style in the electronic environment. The study's purposes are to explore and investigate the availability of cognitive strategy teaching English in google classroom circumstances. The mixed-method design concentrate on the exploratory sequential approach. As a quantitative approach and respondent as a qualitative approach, thirty-seven participants were involved in this study. The study found the adaptability and acceptance of google classroom-feature of collaborative strategic reading, peer-assisted learning strategies, transactional strategies instruction, and concept-oriented reading instruction. The electronic environment of Google Classroom is in one suitable system to establish language pedagogically. English Lecturers would have the opportunity to apply and adjust the cognitive strategy for teaching procedurePedagogical language has shifted dramatically and significantly in these recent pandemic eras. Lecturers could be implemented and adjusted the face-to-face teaching style in the electronic environment. The study's purposes are to explore and investigate the availability of cognitive strategy teaching English in google classroom circumstances. The mixed-method design concentrate on the exploratory sequential approach. As a quantitative approach and respondent as a qualitative approach, thirty-seven participants were involved in this study. The study found the adaptability and acceptance of google classroom-feature of collaborative strategic reading, peer-assisted learning strategies, transactional strategies instruction, and concept-oriented reading instruction. The electronic environment of Google Classroom is in one suitable system to establish language pedagogically. English Lecturers would have the opportunity to apply and adjust the cognitive strategy for teaching procedure